Sleep in women: a narrative review of hormonal influences, sex differences and health implications - Andersen, Monica L.; Hachul, Helena; Ishikura, Isabela Antunes; Tufik, Sergio (Frontiers in Sleep, 2023)
Sleep is a fundamental biological behavior that affects various aspects of health and wellbeing.However, there are some differences in respect of sleep between men and women. Notably, there are sex differences in relation to sleep problems and the potential comorbidities, such as diabetes and cardiovascular diseases, that are associated with these problems, with some evidence suggesting that women may have a greater predisposition to sleep disturbances. This narrative review provides a comprehensive analysis of the literature in respect of sex differences in the sleep, with the main focus being on women. Basic research has investigated sex-specific distinctions in sleep architecture, sleep quality, and circadian rhythms, while clinical studies have examined sex differences in sleep disorders, such as insomnia, sleep apnea, and restless leg syndrome. This narrative review also highlights the impact of the periods of hormonal fluctuations that occur across a woman's lifespan -such as during the menstrual cycle, pregnancy, and menopause phase -and examines their effects on sleep. It also explores the influence of social and cultural factors on sleep patterns in women. Taken together, the evidence suggests that women may be more susceptible to sleep disturbance, and that gender-specific factors should be considered when evaluating sleep in clinical practice. Further research is warranted to elucidate the mechanisms that underlie this and help guide the development of sex-specific interventions to improve sleep quality and promote holistic health in women.